Ectopic Pregnancy - Practise Essentials, Management - A Continuing Cause of Maternal Morbidity - Dr. Priyanka Rahariy, Dr. Vinu Choudhary*, Dr. Surendra Bisu, Dr. Pavitra Sharma, (International Journal of Innovative Research in Medical Science, 2017)
It is currently leading casue of pregnancy related death in 1st trimester. Beside immediate mortality and morbidity, women's future ability to reproduce is also be adversely affected with advent of new diagnostic modalities, early detection and high index of suspicion in ectopic pregnancy morbidity and mortality have considerably declined. Several case report over past few decades revealed that the management of ectopic pregnancy have been revolutionized. A high index of suspicion coupled with early clinical diagnosis supported by tvs and quantitative baseline serum BHCG has paved the way of medical treatment, thereby reducing morbidity and mortality and financial burden casued by it. We are presenting the modalities of management in our institute of patient presenting with ectopic pregnancy over a period of one year from 1 aug 2016 to 1 January 2017. Among 14 patients, majority of them were multi gravid, among which 2 presented with history of infertility treatment. 60% of patient had ampulla as the site of ectopic pregnancy. Among the 14 patient, 3 patients were treated conservative management with inj methotrexate 1mg/kg wt repeat dose every weekly till bhcg.